Day-case adenotonsillectomy for sleep apnoea in children?. Issue 12 (December 2015) - Gan, Richard Wei Chern; Kamani, Tawakir; Wilkinson, Sophie; Thomas, David; Marshall, Andrew H.; Sudarshan, Purushothaman; Daniel, Matija
Abstract: Objectives: Many clinicians are concerned about possible airway or respiratory complications following adenotonsillectomy for sleep related breathing disorder (SRBD), and routinely admit such patients for overnight monitoring. However, published guidelines suggest this is unnecessary in some cases. This study firstly aimed to establish current UK practice, and secondly to investigate whether children with mild/moderate SRBD experience respiratory problems during the first post-operative night. Methods: To establish current UK practice, we carried out a telephone survey asking if the procedure was carried out as a day-case, and admission criteria. For the second aim, a prospective study of children admitted following adenotonsillectomy for mild/moderate SRBD was carried out to investigate occurrence of respiratory complications on first post-operative night. Results: Forty-two UK ENT doctors responded to the telephone survey, 50% routinely admitted patients having adenotonsillectomy for SRBD. Discharge criteria included stable observations and eating and drinking (14 hospitals), no bleeding (1), stable oxygen saturations (1) and age above 5 years (1); four had no specific criteria. Of 51 children admitted following adenotonsillectomy for mild/moderate SRBD, 11 (21.6%) experienced oxygen desaturations overnight. Of these, nine were under 4 years old, and two older children had asthma. Irrespective of comorbidities, 9/27 (33.2%) children under 4 years old experienced desaturations. The only children aged more than 4 years that had desaturations were ones that had additional comorbidities. Conclusion: Half of surveyed doctors admit all children following surgery for SRBD. The number of admissions could be reduced, because same-day discharge for otherwise-healthy children over 4 years old having adenotonsillectomy for mild/moderate SRBD appears to be safe.